The effectiveness of a proposed program based on the story style in developing positive thinking, self-confidence, and a spirit of challenge among fourth-grade students - Drwish, Drwish Hasan (Journal of Educational and Psychological Sciences, 2021)
The current research aims to verify the effectiveness of a proposed program based on the style of the story in developing positive thinking, self-confidence and a spirit of challenge among fourth-grade learners, and it has been adopted to achieve this goal the experimental community, and the main problem of the current research revolves around that negative thinking is more dangerous than any person can imagine, it makes life a series of troubles and negative feelings that multiply and appear either in the form of psychological and organic diseases and a feeling of loss. The study sample consisted of (60) male and female learners from Dr. Rida Saeed School in Damascus Governorate. An educational program was designed based on the style of the story, the positive thinking scale prepared by Ibrahim Abdul Sattar, the Self-Confidence Scale from Schroger numbers, and the Challenge Spirit Scale prepared by the researcher. Previous studies and the theoretical framework on the concept of story and positive thinking among teachers were reviewed, and measures (positive thinking, self-confidence, spirit of challenge) were prepared based on the collected theoretical data. And then judging these metrics by specialists and experts. And the distribution of measures on the exploratory sample of (30) male and female learners. Then check the validity and reliability of the tools. And the distribution of measures to the fourth-grade learners (actual sample). Hence the data analysis and interpretation. The results of the study showed that there were statistically significant differences at the level of significance (0.05) between the mean scores of the learners on the scale (positive thinking, self-confidence, and the spirit of challenge) before and after the implementation of the program. There were statistically significant differences at the level of significance (0.05) between the mean scores of the learners on the scale (positive thinking, self-confidence, and challenging spirit) before and after applying the program, due to the gender variable. Thus, it can be said that the effectiveness of a non-fiction educational program in developing positive thinking, self-confidence and a spirit of challenge among primary fourth-grade learners. Consequently, the research presents a set of recommendations for training teachers in general and teachers of the basic education stage specifically on the style of the story and its educational applications. Preparing model lessons based on the style of the story and clarifying the steps of implementation and the controlled activities.